Aging and the Indian diaspora : cosmopolitan families in India and abroad - Lamb, Sarah (Hyderabad, 2012)
The proliferation of old age homes and increasing numbers of elderly living alone are remarkable new phenomena in India. These trends are related to extensive overseas migration, the transnational dispersal of families amidst global labor markets and the rise of a new Indian middle class. Sarah Lamb's moving and insightful account, based on nearly fifteen years of fieldwork in India and the United States, with a focus on Kolkata, takes us inside India$1 (Bs emerging old age homes and into the households of elders living alone in India and with US-settled children abroad. Lamb also investigates recent state efforts to legally mandate parental care in India and scrutinizes the ways senior Indian Americans make use of and critically reflect upon forms of state-supported elder care prevalent in the United States. Aging and the Indian Diaspora provides an engrossing and vivid portrayal of the innovative and ambivalent ways older Indians and their communities are reworking aging as they confront both embracing and challenging processes they associate with modern, Western and global living. Lamb's study probes debates and cultural assumptions in both India and the United States regarding how best to age; the proper social-moral relationship among individuals, genders, families, the market and the state and ways of finding meaning in the human life course.s
Keywords: East Indian Diaspora